Aspectos resistentes e performáticos nas tragédias medeia, Electra e as Troianas de Eurípedes - PINTO, Rosane Castro (Universidade Federal do Pará, 2021)
This paper presents a study of the tragedies Medea, Electra and The Trojans of Euripides, in which we discuss how the performance and endurance is. We will concentrate on analyzing the female characters the tragic elements and how the narrative is important for understanding the categories violence, memory and oblivion. To understand the theories related to performance, endurance and trauma will use the texts of authors like Jorge Glusberg (1980) which ensures the performance one related to delirium, manifested through the unconscious performer desire, because "the resulting speech is close to delirium and also, truth that is always raving "(Glusberg 1980, p.124). As Sarmento-Pantoja, which states that, the performance can also be considered as a performance built by the characters, "for us this performance can be critical to understand what we call suffering performance" (SARMENTO-PANTOJA, 2002 p.23). Alfredo Bosi notes that resistance is "opposing force itself to external forces" (BOSI, 2002, p. 118) in which we understand as opposition forces that conflict with each other.